Editorial 6.1 - Lefoe, Geraldine (Journal of University Teaching and Learning Practice, 2009)
Welcome to the first issue of Volume Six of the Journal of University Teaching and Learning Practice. This issue contains six papers exploring a range of issues relating to teaching and learning practice and marks my first issue as Senior Editor. I would like to extend our thanks to Associate Professor Helen Carter, who has been Senior Editor of JUTLP since its inception and contributed significantly to the establishment of the journal. This edition also marks a significant change for the organisation of the journal as it is now published through an automated system providing authors, reviewers and editors with up to date information on the submission and review process, allowing authors to track their article through to publication.